The Correlation between Grammar Awareness and Academic Writing Proficiency among EFL Students in the Digital Learning Era - Junita Ulhusna; Ilham Ilham; Lukman Lukman; Irwandi Irwandi (Journal of English Language and Education, 2026)
This study investigates the relationship between grammar awareness and academic writing proficiency among undergraduate EFL students in the digital learning era. Although previous studies have highlighted the importance of grammar awareness in writing, limited research has examined its direct relationship with actual academic writing performance using both metacognitive measures and authentic writing tasks in digital learning contexts. The participants were 50 students from the third and fifth semesters of the English Education Department at Universitas Muhammadiyah Mataram. Grammar awareness was measured using an 18-item Grammar Awareness Questionnaire (GAQ), while academic writing proficiency was assessed through an analytical essay-writing test. Descriptive statistics indicated moderate grammar awareness (M = 42.36) and high academic writing proficiency (M = 85.00). Normality tests confirmed that the data were suitable for parametric analysis. Pearson correlation analysis revealed a very weak and non-significant relationship between grammar awareness and writing proficiency (r = .033, p = .818). Furthermore, simple linear regression analysis showed minimal predictive power of grammar awareness on writing performance (R² = .001). These findings suggest that academic writing proficiency is more likely influenced by other factors, such as vocabulary knowledge, writing strategies, topic familiarity, and academic engagement, rather than grammar awareness alone. Therefore, integrating grammar instruction with explicit writing strategy training is recommended in digital learning environments.